Identification and application of additional restriction fragment length polymorphisms at the human ornithine transcarbamylase locus. - Fox, J E (1986)
Two additional restriction fragment length polymorphisms (RFLPs) have been identified at the human ornithine transcarbamylase (OTC) locus. Approximately 11% of women are heterozygous for an RFLP characterized by polymorphic bands at 3.7 and 3.6 kilobasepairs (kbp) observed after DNA digestion with TaqI. Twenty-nine percent of women are heterozygous for an RFLP characterized by polymorphic bands at 18.0 and 5.2 kbp observed after digestion with BamHI. Thus, in combination with the previously reported RFLPs identified using MspI, the X chromosomes in approximately 80% of women at risk for having a son with OTC deficiency are distinguishable by RFLPs at the OTC locus. Furthermore, we show that these RFLPs will be useful in families for prenatal diagnosis of OTC deficiency, carrier detection, and carrier exclusion.